Reference Intervals for Serum Thyroid-Stimulating Hormone Based on a Recent Nationwide Cross-Sectional Study and Meta-Analysis - Wang, Xichang; Li, Yongze; Zhai, Xiaodan; Wang, Haoyu; Zhang, Fan; Gao, Xiaotong; Liu, Shengyu; Teng, Weiping; Shan, Zhongyan (Frontiers in Endocrinology, 2021)
Objective The aim of our study was to compare the reference intervals (RIs) [median (2.5th-97.5th percentiles)] for thyroid-stimulating hormone (TSH) between subgroups stratified by ethnicity and iodine status in a global context. Design and Methods Primary data were derived from a recently published cross-sectional study in mainland China. Secondary data were obtained from online databases. The RIs for TSH were calculated in the reference population according to the National Academy of Clinical Biochemistry (NACB) standard and in the disease-free population. A meta-analysis of ethnicity- and iodine status-specific TSH RIs was performed. Results The primary data showed that the TSH RI (mU/L) in the disease-free population was 2.33 (0.67, 7.87), which is wider than the published RI [2.28 (0.74, 7.04)] in the reference population. The meta-analysis showed that whether in the reference or disease-free population, the RIs in Yellows were much higher than those in Caucasians. In the reference population, the median and 2.5th percentile in the iodine-sufficient subgroup were both lower than the iodine-deficient or more-than-adequate subgroup, while the 97.5th percentile showed a positive trend with increasing sufficiency of iodine. However, in the disease-free population, the iodine-sufficient subgroup had a lower median and 97.5th percentile but higher 2.5th percentile than the iodine-deficient subgroup. Conclusion Yellows have a higher TSH RI than Caucasians. In the reference population, both the median and 2.5th percentile TSH in the iodine-sufficient population were the lowest among the different iodine status subgroups, while the 97.5th percentile of TSH showed an upward trend with increasing iodine sufficiency.